A Pyrene‐Linked Cavity within a β‐Barrel Protein Promotes an Asymmetric Diels–Alder Reaction. (31st August 2017) - Himiyama, Tomoki; Taniguchi, Naomasa; Kato, Shunsuke; Onoda, Akira; Hayashi, Takashi
Abstract: A unique π‐expanded reaction cavity tethering a polycyclic moiety which provides a platform for substrate binding was constructed within the robust β‐barrel structure of nitrobindin (NB). NB variants with cavities of different sizes and shapes are coupled with N ‐(1‐pyrenyl)maleimide (Pyr ) to prepare a series of NB‐Pyr conjugates. The orientation of the pyrene moiety is fixed within the cavity by the coupling reaction. The fluorescent quenching analysis of NB‐Pyr indicates that azachalcone (aza ), which is a dienophile for a Diels–Alder (DA) reaction, is efficiently incorporated within the pyrene‐linked reaction cavity by the aromatic interaction. The DA reaction betweenaza and cyclopentadiene proceeds within the reaction cavity of NB‐Pyr in the presence of Cu II ion in high yield and high enantio‐ and regioselectivity.